Calcium pyrophosphate crystal size and characteristics - Monica Zell, MD; Thanda Aung, MD, MS; Marian Kaldas, MD; Ann K. Rosenthal, MD; Bijie Bai; Tairan Liu; Aydogan Ozcan, PhD; John D. FitzGerald, MD, PhD (Osteoarthritis and Cartilage Open, 2021)
Objective: To describe the characteristics of calcium pyrophosphate (CPP) crystal size and morphology under compensated polarized light microscopy (CPLM). Secondarily, to describe CPP crystals seen only with digital enhancement of CPLM images, confirmed with advanced imaging techniques. Methods: Clinical lab-identified CPP-positive synovial fluid samples were collected from 16 joint aspirates. Four raters used a standardized protocol to describe crystal shape, birefringence strength and color. A crystal expert confirmed CPLM-visualized crystal identification. For crystal measurement, a high-pass linear light filter was used to enhance resolution and line discrimination of digital images. This process identified additional enhanced crystals not seen by raters under CPLM. Single-shot computational polarized light microscopy (SCPLM) provided further confirmation of the enhanced crystals’ presence. Results: Of 932 suspected crystals identified by CPLM, 569 met our inclusion criteria, and 293 (51%) were confirmed as CPP crystals. Of 175 unique confirmed crystals, 118 (67%) were rods (median area 3.6 ​μm2 [range, 1.0–22.9 ​μm2]), and 57 (33%) were rhomboids (median area 4.8 ​μm2 [range, 0.9–16.7 ​μm2]). Crystals visualized only after digital image enhancement were smaller and less birefringent than CPLM-identified crystals. Conclusions: CPP crystals that are smaller and weakly birefringent are more difficult to identify. There is likely a population of smaller, less birefringent CPP crystals that routinely goes undetected by CPLM. Describing the characteristics of poorly visible crystals may be of use for future development of novel crystal identification methods.